2013
DOI: 10.1149/2.027306jes
|View full text |Cite
|
Sign up to set email alerts
|

Correlating Microstructure and Activity for Polysulfide Reduction and Oxidation at WS2Electrocatalysts

Abstract: The polysulfide reduction and oxidation activity of WS2 electrocatalysts was studied. This was undertaken with a specific view to improve the efficiency of the polysulfide-bromine redox flow battery, for large scale energy storage. Using data from the literature, it is estimated that the catalysts would require exchange current densities of ∼0.7 to 1 mA cm−2 true microscopic surface area to enable them to become economically viable. The experiments were performed upon three different forms of WS2: platelet lik… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 106 publications
0
20
0
Order By: Relevance
“…It is widely known that the unsaturated coordinated planes (active sites) and d-band characteristic present in transition metal/dichalcogenides are responsible for catalytic activity and is proved in several electrochemical reactions. Similarly, the aqueous PS redox process is activated by using catalytic surface in solar cell , and flow battery applications which support the surface involved electrocatalysis of sulfur redox process in the Li–S cell.…”
Section: Resultsmentioning
confidence: 91%
“…It is widely known that the unsaturated coordinated planes (active sites) and d-band characteristic present in transition metal/dichalcogenides are responsible for catalytic activity and is proved in several electrochemical reactions. Similarly, the aqueous PS redox process is activated by using catalytic surface in solar cell , and flow battery applications which support the surface involved electrocatalysis of sulfur redox process in the Li–S cell.…”
Section: Resultsmentioning
confidence: 91%
“…It is well known that the insulating nature of polysulfides causes poor reaction kinetics and hence influences overall redox process. On the other hand, use of electrocatalytic electrodes has found to enhance the reaction kinetics of aqueous polysulfides in photoelectrochemical solar cells 30 31 32 33 34 and redox flow cells 35 36 37 38 39 . However, to the best of our knowledge, there have been no reports on utilizing electrocatalysis concept in non-aqueous polysulfides redox reactions.…”
mentioning
confidence: 99%
“…The specific surface area of ta-WS 2 was 75.5 m 2 g −1 , while the pristine WS 2 merely possessed a surface area of 15.6 m 2 g −1 . Because the catalyst activity was directly proportional to the number of edge planes at the catalyst surface for polysulfide redox reactions [38], the ta-WS 2 with the higher specific surface area accompanied more active sites or edge planes, which greatly improved the catalytic performance in the polysulfide system. Also, the smaller size of ta-WS 2 is beneficial to form effective electron pathways from conductive framework to the electrocatalyst surface, which results in the lower charge transfer resistance and ensures the higher utilisation of polysulfides.…”
Section: Resultsmentioning
confidence: 99%
“…These investigations have shown that the surface chemistry of WS 2 is closely related toward high catalytic activity or high ion storage performance. More importantly, different forms of WS 2 as the electrocatalysts for polysulfide reduction and oxidation were studied, which reported that the catalyst activity was directly proportional to the number of edge planes at the catalyst surface [38]. Furthermore, transition metal dichalcogenides, owing to their strong chemical affinity with polar polysulfide species, are found to play an anchoring effect in the organic electrolyte-based lithium-sulfur batteries, which can introduce intimate contact with polysulfides and thereby facilitate the polysulfide redox reactivity [26,39,40].…”
mentioning
confidence: 99%